Gitar Sebagai Bentuk Dining Table dengan Penerapan Ornamen Jepara - Amirul Mukminin; Jati Widagdo (SULUH: Jurnal Seni Desain Budaya, 2018)
Human do many activity everyday, such as eating and drinking, and also dinner as a habit in the evening. Writer has ever seen that people drinking while playing guitar, this thing to inspire him to design a product base guitar as an idea. Jepara has many cultures, one of them named Jepara ornament. The problem appears is human need product to facility eating and drinking also dinner, by combining between furniture and guitar, developing Jepara ornament. Kind of data that writer need are: dining table data, guitar data, ornament data. Writer uses qualitative method with approach: literature study, interview, survey. The research result is guitar body made as a table body, hanger as a leg table, Jepara ornament applies by inlay, finish color is salak brown. The conclusion is combining furniture and guitar are interested too, and could function as eating and drinking facility. If Jepara ornament applies by inlay it could be good as well.